INDONESIAN EFL COLLEGE STUDENTS’ ANXIETY IN ENGLISH ORAL PRESENTATIONS: FACTORS OF ANXIETY AND STRATEGIES TO COPE WITH ANXIETY - Herusatoto, Hesthi; Nurtia, Siti (Conscientia - Journal on Language, Literature, and Culture, 2025)
This descriptive qualitative research examined the anxiety of students majoring in English literature when giving an oral presentation in English. The fifth and seventh semester students were the subjects of research. Observations, interviews, and questionnaires were used to identify factors causing anxiety among the students in their oral presentations in class and to study their strategies to overcome anxiety. The results reveal that fear of making mistakes, shyness, lack of self-confidence, lack of motivation, embarrassment, limited vocabulary, grammatical errors, peer influence, lack of preparation, teacher's presence, and lack of experience were factors contributing to the students' anxiety. Anxiety was also influenced by the attitude of the class teacher, which can either boost students' confidence or reinforce their worry. To overcome their anxiety, the EFL students applied memory, cognitive, compensation, metacognitive, affective, and social strategies. Many students, particularly those who practiced, reflected on themselves, or asked for criticism, developed progressive confidence.